Penggunaan TVP dan Aplikasi Pasteurisasi dalam Pembuatan Sosis Sapi Goreng di PT. X - Akbar Pradana; Joko Hermanianto; Sugiyono Sugiyono (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
Abstract. With the price of beef that fluctuates from time to time, Company ‘X’ attempted the innovation with analog meat or Textured Vegetable Protein (TVP) to replace some of percentage of meat used in the formula. The objective of this research is to create fried beef sausage formula with TVP to improve the cost and understand the effectiveness of pasteurization for the product to extend the shelf life. This research showed that 2% of TVP can replace 7% of meat from the total meat used in the existing formula of fried beef sausage. This research also proved the result from the application of 30 minutes pasteurization for both fried beef sausage formula with TVP and the existing one. Fried beef sausage with pasteurization application can achieve 45 days of shelf life compare to the existing formula without pasteurization application only only 30 days and can reduce 9% of the cost and decrease the product return from the market due to spoilage from 4% to 0.5%. Keywords: fried beef sausage, Textured Vegetable Protein (TVP), pasteurization DOI: https://doi.org/10.29244/jmpi.2019.6.99